2018 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2018
DOI: 10.1109/robio.2018.8664858
|View full text |Cite
|
Sign up to set email alerts
|

Reactive velocity control reduces energetic cost of jumping with a virtual leg spring on simulated granular media

Abstract: Robots capable of dynamic locomotion behaviors and high-bandwidth sensing with their limbs have a high cost of transport, especially when locomoting over highly dissipative substrates such as sand. We formulate the problem of reducing the energetic cost of locomotion by a Minitaur robot on sand, reacting to robot state variables in the inertial world frame without modeling the ground online. Using a bulkbehavior model of high-velocity intrusions into dry granular media, we simulated single jumps by a onelegged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…This equation describes the "power function" of the ground, or the rate at which energy is physically transferred from the foot to the ground. See Roberts and Koditschek (2018) for a more detailed derivation.…”
Section: Description Of the Compression-extension And Active Damping Controllersmentioning
confidence: 99%
See 2 more Smart Citations
“…This equation describes the "power function" of the ground, or the rate at which energy is physically transferred from the foot to the ground. See Roberts and Koditschek (2018) for a more detailed derivation.…”
Section: Description Of the Compression-extension And Active Damping Controllersmentioning
confidence: 99%
“…In previous work (Roberts and Koditschek, 2018;Roberts and Koditschek, 2019) we introduced a reactive controller for sand locomotion that uses a new variant of active damping to reduce the energetic cost of transport (see Section 2.2) and performed initial tests using a one-legged robot in simulation and emulation. In Roberts and Koditschek (2018) we introduced the reactive controller and showed in simulation that it reduced the energy necessary to jump on granular media relative to its base controller when varying forces from the ground and initial conditions. In Roberts and Koditschek (2019) we built a robotic platform that emulates the forces exerted by a simplified granular media model and tested a physical robot jumping with the active damping controller, varying the robot's jump height.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For legged locomotors on yielding terrain, ground deformation due to foot penetration constitutes an irrecoverable energy loss, so minimizing foot penetration depth is relevant to energy-efficient locomotion. Recent research ( [1,2,3,4]) has addressed jumping from rest on yielding terrain, i.e., the stanceto-flight transition. Here, conversely, we address the flightto-stance transition, focusing specifically on the challenge of minimizing foot penetration depth.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hubicki et al [2] demonstrated that jumping on granular media could be improved by incorporating a dynamic model of the ground reaction force (GRF) into the robot dynamics used by optimization-based motion planning algorithms. Although previous studies examined jumping from rest (e.g., [1], [2]) and cyclic hopping (e.g., [3], [4]) on yielding substrates, this paper focuses specifically on minimum-penetration-depth landing, which to the best of our knowledge has yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%